(untitled) - Bailey, Brian J.; (1925-2012) (Malaysia, 1999)
The Lord Jesus in His teachings of the Second Coming gives numerous warnings of false prophets and deceptions. We need to heed these warnings seriously. Much despair and confusion have been caused by the books written, seminars given, and visions shared, which predict the days and times of the Lord's return.Dr. Brian J. Bailey presents in The Second Coming as an easy way to read and an understandable guide to the series of events that must occur before the Lord comes
Keywords: Second Advent